2009
DOI: 10.1590/s0100-39842009000400011
|View full text |Cite
|
Sign up to set email alerts
|

Refluxo gastroesofágico: estudo comparativo da receptividade e sensibilidade entre seriografia e ultrassonografia

Abstract: OBJECTIVE: Comparative study of receptiveness (cooperation) and sensitivity of upper gastrointestinal series and intraabdominal esophagus ultrasonography in patients with suspicion of gastroesophageal reflux. MATERIALS AND METHODS: The present study included 42 pediatric patients (26 male, with mean age of 33.64 ± 34.33 months, and 16 female, with mean age of 31.02 ± 35.56 months) with suspicion of gastroesophageal reflux, who were initially submitted to upper gastrointestinal series and subsequently to intraa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
1
0
2
Order By: Relevance
“…There was a diversity of topics in the medical research found, from food thickening¹, corporal posture 13,29 , diagnosis 14,31 , treatments 26,32,35 to exams 15,19,20,22,2 , among others.…”
Section: Discussionmentioning
confidence: 99%
“…There was a diversity of topics in the medical research found, from food thickening¹, corporal posture 13,29 , diagnosis 14,31 , treatments 26,32,35 to exams 15,19,20,22,2 , among others.…”
Section: Discussionmentioning
confidence: 99%
“…Estudiosos afirmam que o conteúdo gástrico refluído pode causar através de micro ou macroaspirações a tosse, ou ainda estimular o reflexo vagal e a liberação de taquicinina. (3,10,15,17,18) Outros sintomas, ainda observados com frequência foram o distúrbio do sono, regurgitações, a dor abdominal e a dispneia, esta com pouca significância já que a literatura não cita como um sintoma e sim como um sinal, talvez decorrente de uma obstrução nasal, (9) fato observado no nosso estudo, pois as crianças constantemente e com facilidade apresentavam quadro gripal. Outros estudos afirmam que a dor abdominal e a regurgitação são sintomas comuns na DRGE.…”
Section: Discussionunclassified
“…É um método não invasivo, seguro e não utiliza a radiação ionizante. (19,20) No entanto a pHmetria é considerada o método padrão ouro, pois detectam a presença, frequência, duração e gravidade da DRGE, porém está sujeito a críticas, já que demonstram variações significativas na sensibilidade do método, (9,20,21,22) no presente estudo foi o segundo exame mais solicitado para o diagnóstico. As característica da endoscopia digestiva como um alto índice de sensibilidade, cerca de 60%, a facilidade de execução e disponibilidade na maioria dos centros médicos, além de ser excelente para diagnosticar lesões do esôfago, faz com que este método diagnostico fique conhecido como padrão ouro para detectar complicações e excelente para confirmar a DRGE.…”
Section: Discussionunclassified